A Framework for Management and Monitoring of QoS-based Cloud Services - Modi, KJ; Chowdhury, DP (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides dynamic and scalable environment for the benefit of end users to offer services which are known as cloud services. Due to on- demand, scalability low operational cost benefits the customers using cloud service is increasing day by day. Thus, the biggest and major challenges in the cloud environment is maintaining the Quality-of-Service (QoS), where cloud provider has to manage the resources in such a way that they will able to provide promised QoS metrics such as, performance, availability, reliability and cost. Cloud services are offered depends on Service Level Agreements (SLAs), an official agreement between cloud provider and user. To measure what quality of the services is offered by the cloud provider, we require monitoring the cloud computing services. Monitoring is important for both customer and service provider. The monitoring status helps cloud provider to improve their services and also helps the customer to know whether they are receiving the promised QoS or not. In this paper, we proposed the general framework and addressed the different aspects related to management and monitoring of QoS-based cloud computing services. We also discuss the key issues and challenges of QoS-based cloud services.